EVALUASI PENERAPAN REKAM MEDIS ELEKTRONIK DI UNIT RAWAT JALAN RUMAH SAKIT PANTI WALUYA MALANG - Biakna Jaya, Angela Floresta Tirtha Amarta; Anugrahanti , Wisoedhanie Widi; Aini, Nita Dwi Nur (ASSYIFA : Jurnal Ilmu Kesehatan, 2025)
Currently, the advancement of information technology is growing rapidly in all service sectors, including in the health sector, one of which is hospitals. Hospitals are the front line of referral health services for the community. Every hospital has an obligation, one of which is to organize medical records. All health service facilities are required to implement Electronic Medical Records and it is expected that the implemented information systems can be integrated with each other to become an integrated health information system. Panti Waluya Hospital Malang is one of the hospitals that implemented Electronic Medical Records on June 1, 2023. This study uses a quantitative type with a descriptive approach, which was carried out in April 2024. The sampling technique in this study uses the Proportionate Stratified Random Sampling approach. From the results of the questionnaire, the results of the usefulness aspect were 88% with a good category, the convenience aspect 62% with a sufficient category, the interest aspect 86% with a good category and the actual aspect 81% with a good category.